2014
DOI: 10.1371/journal.ppat.1004053
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Macrophages Are Essential for Protection from Respiratory Failure and Associated Morbidity following Influenza Virus Infection

Abstract: Alveolar macrophages (AM) are critical for defense against bacterial and fungal infections. However, a definitive role of AM in viral infections remains unclear. We here report that AM play a key role in survival to influenza and vaccinia virus infection by maintaining lung function and thereby protecting from asphyxiation. Absence of AM in GM-CSF-deficient (Csf2 −/−) mice or selective AM depletion in wild-type mice resulted in impaired gas exchange and fatal hypoxia associated with severe morbidity to influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
278
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(309 citation statements)
references
References 60 publications
11
278
1
Order By: Relevance
“…These results are in agreement with those of several previous studies in which neutrophil depletion did not alter viral replication or body weight loss (39)(40)(41)(42). However, macrophage depletion studies (including our own) have generally shown that macrophage depletion increases viral replication, which contrasts with our current findings (24,(43)(44)(45)(46). The underlying reason for this discrepancy is unclear, although it may indicate that, despite being attenuated, the macrophage response to infection in A 1 -KO mice may nevertheless be sufficient to control viral replication.…”
Section: Fig 7 Lung Compliance and Airway Resistance Were Not Alteredsupporting
confidence: 93%
“…These results are in agreement with those of several previous studies in which neutrophil depletion did not alter viral replication or body weight loss (39)(40)(41)(42). However, macrophage depletion studies (including our own) have generally shown that macrophage depletion increases viral replication, which contrasts with our current findings (24,(43)(44)(45)(46). The underlying reason for this discrepancy is unclear, although it may indicate that, despite being attenuated, the macrophage response to infection in A 1 -KO mice may nevertheless be sufficient to control viral replication.…”
Section: Fig 7 Lung Compliance and Airway Resistance Were Not Alteredsupporting
confidence: 93%
“…Thus, the response of these cells to IAV infection is likely to be of critical importance to disease outcome. The importance of macrophages for protection against IAV infection is well established, as ablation of macrophages enhances IAV-associated immunopathology and mortality [8][9][10][11][12]. The importance of macrophages during IAV infection goes beyond protection from virus-induced pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 AMs are known to be required to induce protective immune responses against bacteria, fungi, and viruses. 13 Dendritic cells (DCs) together with AMs are major antigen-presenting cells in the lungs. Respiratory DCs play a crucial role in inducing adaptive immune responses.…”
Section: Introductionmentioning
confidence: 99%